2002
DOI: 10.1002/jnr.10173
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the “C” and “T” alleles of the 5‐HT2A receptor gene in the temporal cortex of normal individuals and schizophrenics

Abstract: A genetic association between schizophrenia and a silent C/T(102) polymorphism in the 5-HT2A receptor gene (5-HT2AR) has been previously reported; however, the mechanisms underlying this association remain unknown. Here we developed an improved quantitative assay for measurements of allele ratios, which revealed that the expression of allele "C" in the temporal cortex of normal heterozygous individuals was significantly lower than the expression of allele "T" (allele "C" to allele "T" ratio of approximately 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
1
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(166 citation statements)
references
References 39 publications
8
153
1
4
Order By: Relevance
“…The TT genotype is associated with more 5-HT 2A receptors in healthy volunteers but apparently not in the mood disorders group even though there was the same rank order of binding by genotype (TT4TC4CC). This finding is consistent with Polesskaya and Sokolov (2002), who studied the relationship of the C and T alleles to the expression of the HTR 2A gene in post-mortem brain tissue and found the expression level with the T allele was higher compared with the C allele in schizophrenia and a control group. They did not include a sample with mood disorders.…”
Section: -Htr 2a Gene Polymorphism and Receptor Binding Vd Khait Et Alsupporting
confidence: 90%
See 1 more Smart Citation
“…The TT genotype is associated with more 5-HT 2A receptors in healthy volunteers but apparently not in the mood disorders group even though there was the same rank order of binding by genotype (TT4TC4CC). This finding is consistent with Polesskaya and Sokolov (2002), who studied the relationship of the C and T alleles to the expression of the HTR 2A gene in post-mortem brain tissue and found the expression level with the T allele was higher compared with the C allele in schizophrenia and a control group. They did not include a sample with mood disorders.…”
Section: -Htr 2a Gene Polymorphism and Receptor Binding Vd Khait Et Alsupporting
confidence: 90%
“…Turecki et al (2003) found that higher 5-HT 2A binding in the brain is associated with the T102C polymorphism in the 5-HT 2A gene independently of suicide, although others disagree (Hrdina and Du, 2001). The T and C alleles may show differential expression (Polesskaya and Sokolov 2002;Bray et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, disease risk alleles can be mapped by taking advantage of LD relationships to neighboring alleles of genetic markers, and, this way, multiple silent polymorphisms have been found to be associated with human diseases [30]. For example, a link has been found between the silent SNP 102C/T of the 5-HT2A receptor gene in the temporal cortex and the pathogenesis of schizophrenia [31]. Jones and colleagues have shown that silent polymorphisms of the angiotensin-2 receptor increase cardiovascular risk in hypertension [32], while Arriba-Mendez and colleagues have found that when the C allele is present in the silent SNP 927T/C, male children may be predisposed to asthma and atopic dermatitis [33].…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, the distinct association between the 5-HT2A receptor 102T-C polymorphism and pure PD in Estonian and Japanese samples may point to a specific influence of this genetic variant on predisposition to pure PD that may lose its strength in comorbid phenotypes of PD. There is also an observation that the C allele has a lower expression than the T allele, indicating a functional role for the 102T-C polymorphism (Polesskaya and Sokolov, 2002). The association with the lower expressive activity allele of the 5-HT2A gene, as well as the failure of therapeutic effects or even symptomatic exacerbation in the case of 5-HT2A antagonists in patients with PD, point to the possible beneficial effects of 5-HT2A agonism in the treatment of PD.…”
Section: -Ht Receptor Genesmentioning
confidence: 99%